Constraints Faced by the Farmers in Utilizing Raitha Samparka Kendras (RSKs): An Extension Services - , P. V. Sachin, S. L. Patil, Pavan. M. K (Archives of Current Research International, 2024)
A survey of 210 farmers in Haveri district, Karnataka, was undertaken to investigate the constraints they encountered in utilizing the extension services provided by the Department of Agriculture during 2018-19. The constraints encountered by farmers were categorized into five major categories. The study revealed that, in terms of information services, over two-thirds (71.90%) of the farmers reported a lack of available extension workers in their offices and irregular visits to villages and fields. This indicates a significant gap in the availability and accessibility of information resources for farmers. Majority of the farmers (73.33%) reported that time constraints prevented them from participating in extension activities offered by RSKs, followed by more than half (58.57%) of the respondents who expressed that the location of extension activities was inconvenient. Regarding input services availed by farmers 70.00 per cent of farmers expressed non availability of required inputs (variety, chemical). Additionally, over three-quarters of farmers expressed dissatisfaction with the distance between their villages and Rural Service Centers (RSKs), making it difficult to access diagnostic services and technical support. Regarding developmental activities, a significant number of farmers, 77.14 per cent, reported delays in the construction of Krishi-Honda (agricultural machinery). Additionally, over two-thirds of farmers expressed dissatisfaction with the lack of access to drip and sprinkler irrigation sets for all categories of farmers. These constraints hinder the adoption of modern agricultural practices and limit the potential for increased productivity and income.